2003
DOI: 10.1076/ceyr.26.4.303.15425
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hemodialysis on visual field test in patients with chronic renal failure

Abstract: Visual field testing should be done after hemodialysis in patients who are on regular hemodialysis program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 5 publications
0
31
0
3
Order By: Relevance
“…7 Some studies reported that there is no correlation between mOsm and IOP, while others reported no change in IOP during HD. 10,11,13,16 Tokuyama et al observed a decrease in IOP (−1.8 mm Hg) and plasma osmolarity following HD, but not a significant correlation between IOP and plasma osmolarity; however, they did note a correlation between IOP and plasma colloid osmotic pressure (r = −0.510, p = 0.0012) and a change in body weight (r = 0.534, p = 0.0006). 9 According to Fauchald, plasma colloid osmotic pressure is critical to hydrodynamic changes during HD.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…7 Some studies reported that there is no correlation between mOsm and IOP, while others reported no change in IOP during HD. 10,11,13,16 Tokuyama et al observed a decrease in IOP (−1.8 mm Hg) and plasma osmolarity following HD, but not a significant correlation between IOP and plasma osmolarity; however, they did note a correlation between IOP and plasma colloid osmotic pressure (r = −0.510, p = 0.0012) and a change in body weight (r = 0.534, p = 0.0006). 9 According to Fauchald, plasma colloid osmotic pressure is critical to hydrodynamic changes during HD.…”
Section: Discussionmentioning
confidence: 94%
“…Many published studies reported changes in IOP based on measurements obtained using a Goldmann applanation tonometer. 7,9,11,13,14 Patients must be seated when using a Goldmann applanation tonometer. The reduction in blood volume that occurs during HD can cause hypotension and any movement during HD can cause blood pressure variation, all of which can indirectly affect IOP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the works with the larger number of patients, [3][4][5][6][7][8]13,15,[18][19][20][26][27][28][29][30] statistical analysis of the results were performed, resulting in a more supported basis for the proposed conclusions and mechanisms of IOP changes during HD. But in spite of this statistical analysis, opposite findings were found, as we mentioned before.…”
Section: Discussionmentioning
confidence: 99%
“…ise KBY hastalarında hemodiyalizin vücuttaki hipervolemi ve serum elektrolit seviyelerini düzelterek, görme alanı global değerlerinde olumlu etkiye sebep olduğunu, ve glokomu olan hemodiyaliz hastalarını hemodiyaliz sonrası yapılacak görme alanı testi ile değerlendir-mek gerektiğini bildirmişlerdir. 24 Çalışmamızda Fourier prensibi ile çalışan OKT cihazı ile hemodiyaliz öncesi RSLT ölçümü referans alınarak hemodiyaliz sonrası RSLT ölçümleri değerlendirildi, ve tüm segmentlerde RSLT kalınlığında artış saptandı. Ancak bu artış sadece RSLT kalınlığının daha ince olduğu nazal ve temporal segmentlerde istatistiksel olarak anlamlı değildi.…”
Section: Discussionunclassified